Research on thermal characteristics of heat pipes for led lightning devices - Lozovoi, M. A.; Nikolaenko, Yu. E.; Rassamakin, B. M.; Khairnasov, S. M. (Technology and design in electronic equipment, 2014)
New energy-saving technologies for lighting is a promising trend in lighting technology. To this end, during the recent decade, have been actively developed and implemented lighting units based on LED modules. Reliability of such devices is largely dependent on the ensuring of cooling of the LEDs. Heat pipes are being used with ever-increasing frequency for increasing an efficiency of cooling of powerful LEDs within a lightening device. Results of experimental modelling of thermal characteristics of two aluminium heat pipes with grooved capillary structure and ammonia used as a heat transfer agent, designed for application as a heat transfer elements in designs of powerful LED lightening device with forced air cooling are presented in this paper. It is shown that for the heat flux range of 50 to 100 W and for incident flow speed in the range of 0.8 to 2.1 m/s the temperature in the heating zone of the heat pipe falls into the range of 31.0 to 52.5 °C. In this case the temperature difference along the heat pipe is between 0.9…1.7 °C, when a minimal value of the fed heat flux is 50 W, and 1.7…3.1°C, when a maximum value of the heat flux is 100 W. The value of heat transfer resistance of the heat pipes was in the range of 0.012 to 0.044 °C/W. The key factors influencing the thermal characteristics of the heat pipes are: the value of the fed heat flux, the speed of cooling air flux, heat pipe inclination angle with respect to the horizon. By using five such heat pipes within the powerful LED lightning device it is possible to achieve an elimination of the total heat flux from LED modules up to 500 W. At an efficiency factor of LEDs of about 75% this is equivalent to intake power 665 W. Taking into account that luminous efficiency of modern LEDs is about 10 times as high as those of incandescent lamps, proposed lightning device will produce a luminous flux which is equivalent to the luminous flux of a lightening device with incandescent lamps with a power of 6650 W, so that this will allow reducing an input power of the lightening device by 5985 W.